Correlation between jump height and biomechanical variables in Chilean athletes of team sports - Bustamante, A.; Aedo-Muñoz, E.; Fuenzalida, P.; Cerda-Kohler, H.; Moya-Jofre, C.; Araya-Ibacache, M.; Garcia de la Pastora, D.; Torres, M. (ISBS Proceedings Archive (Michigan), 2023)
In elite team sports technical skills and explosiveness are essential to get the optimum performance, being the vertical jump one of the most important motor skills in competition, usually assessed by countermovement jump (CMJ). The main aim of our study is to determine the correlation between jump height and kinetic and kinematic variables using force platforms, and secondly to describe CMJ values of elite Chilean team sports athletes. The results obtained in our study showed a positive correlation between jump height and concentric mean power, concentric peak velocity, concentric peak power and total concentric impulse. These results are fundamental for an optimal analysis of athletes jumping tests, based on data from the specific study population and the use of those variables that are most related to their performance.